Impact of knowledge management system on knowledge Centric Organization Productivity - C. A. Malarvizhi; Sreenivasan Jayashree; Amin Rasti; Abdullah Al- Mamun; Shabnam Mayel (2015)
Introduction Knowledge has been referred to as a key organizational asset(Lee et all., 2009) and its management as a result, falls into the highest priority of the organization (Goa et all.,2014). In order for companies to utilize the knowledge, a knowledge management system has to knowledge (Alavi and Leidnerbe, 2001) implemented to capture, store, and assign the existing. This process is vital to existence of the knowledge centric organizations; as the primary source of business is the individual’s knowledge which functions an asset in such companies (Zack, 2003).